Scarred but Wiser World War 2's COVID Legacy - Lokshin, Michael (The World Bank, 2020)
The paper formalizes and tests the hypothesis that greater exposure to big shocks induces stronger societal responses for adaptation and protection from future big shocks. Support for this hypothesis is found in various strands of the literature and in new empirical tests using cross-country data on deaths due to COVID-19 and deaths during World War 2. Countries with higher death rates in the war saw lower death rates during the COVID-19 pandemic. The tests are robust to a wide range of model specifications and alternative assumptions